Regarding the coronavirus precautions taken by the employer - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the precautions taken to prevent coronavirus contamination during BRACU new campus project work.